Types of evidence syntheses - Graf, S.; Kranz, J.; Schmidt, S.; Uhlig, A.; Bellut, Laura (Urologe, 2021)
This manuscript outlines various types of review articles as forms of evidence synthesis with special regard to their strengths and limitations. Review articles not only present summarised data, but also offer an evaluation of the quality of the individual studies included in it. The validity and the reliability of outcomes of reviews is strongly dependent on the quality of the data included. For this reason, a comprehensive literature selection process is paramount. Fundamental knowledge of bias and literature assessment is also necessary when reading reviews. This article presents selected tools for evidence appraisal and evaluation of bias risk.
CRIS-Team WoS Importer:2021-04-09